2018
DOI: 10.2337/db18-2221-pub
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diuretics Use and Amputations in Patients with Type 2 Diabetes—A Hypothesis Driven from Canvas Warning?

Abstract: Clinical trials in patients with type 2 diabetes (T2D) showed that the incidence of lower limb amputations (LLA) was doubled in patients in canagliflozin arm compared with placebo. Whether hypovolemia favored by SGLT2 inhibition-induced diuresis could be associated with a reduced lower extremity perfusion is a potential explanation. Although we cannot test this hypothesis directly, a similar side-effect of diuretics would be a supportive argument. We tested the association between use of diuretics (recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies that evaluate the biological mechanisms that could account for any such risk of SGLT2i's are also needed. For example, it is unclear whether any increased risk of amputation, should it be present, is due to the diuretic effect of SGLT2i's; some studies have suggested that diuretics may increase the risk of amputations in patients with type 2 diabetes [48] [49].…”
Section: Plos Onementioning
confidence: 99%
“…Studies that evaluate the biological mechanisms that could account for any such risk of SGLT2i's are also needed. For example, it is unclear whether any increased risk of amputation, should it be present, is due to the diuretic effect of SGLT2i's; some studies have suggested that diuretics may increase the risk of amputations in patients with type 2 diabetes [48] [49].…”
Section: Plos Onementioning
confidence: 99%